How do circadian rhythms and neural synchrony shape networked cooperation? - Vasiliauskaite, Vaiva; Hausladen, Carina I. (Frontiers in Physics, 2023)
This paper investigates the effects of temporal changes at the individual and the social level and their impact on cooperation in social networks. A theoretical framework is proposed to explain the probability of cooperation as a function of endogenously-driven periodical temporal variation and neural synchrony modeled as a diffusion process. Agents are simulated playing a Prisoner's dilemma game with and without evolution, in a two-player setting and on networks. Most importantly, we find that temporal variation and synchrony influences cooperation patterns in a non-trivial way and can enhance or suppress cooperation, depending on exact parameter values. Furthermore, some of our results point to promising future research on human subjects: Specifically, we find that cooperators can dramatically increase their payoff—as opposed to defectors—if neural synchrony is present. Furthermore, the more heterogeneous the synchrony between two agents, the less they cooperate. In a network setting, neural synchrony inhibits cooperation, and variation in circadian patterns counter-acts this effect.